Coding variants in NOD-like receptors: An association study on risk and survival of colorectal cancer - Huhn, Stefanie; da Silva Filho, Miguel I; Sanmuganantham, Tharmila; Pichulik, Tica; Catalano, Calogerina; Pardini, Barbara; Naccarati, Alessio; Polakova-Vymetálkova, Veronika; Jiraskova, Katerina; Vodickova, Ludmila; Vodicka, Pavel; Löffler, Markus W; et al. (PloS one, 2018)
Nod-like receptors (NLRs) are important innate pattern recognition receptors and regulators of inflammation or play a role during development. We systematically analysed 41 non-synonymous single nucleotide polymorphisms (SNPs) in 21 NLR genes in a Czech discovery cohort of sporadic colorectal cancer (CRC) (1237 cases, 787 controls) for their association with CRC risk and survival. Five SNPs were found to be associated with CRC risk and eight with survival at 5% significance level. In a replication analysis using data of two large genome-wide association studies (GWASs) from Germany (DACHS: 1798 cases and 1810 controls) and Scotland (2210 cases and 9350 controls) the associations found in the Czech discovery set were not confirmed. However, expression analysis in human gut-related tissues and immune cells revealed that the NLRs associated with CRC risk or survival in the discovery set were expressed in primary human colon or rectum cells, CRC tissue and/or cell lines, providing preliminary evidence for a potential involvement of NLRs in general in CRC development and/or progression. Most interesting was the finding that the enigmatic development-related NLRP5 (also known as MATER) was not expressed in normal colon tissue but in colon cancer tissue and cell lines. Future studies may show whether regulatory variants instead of coding variants might affect the expression of NLRs and contribute to CRC risk and survival.
Keywords: genetické asociační studie; genetická predispozice k nemoci; senioři; Aged; Male; Gene Expression Regulation, Neoplastic; lidé; Humans; Genetic Variation; Polymorphism, Single Nucleotide; jednonukleotidový polymorfismus; otevřené čtecí rámce; Czech Republic; NLR Proteins; Colorectal Neoplasms; hematopoéza; genetická variace; mužské pohlaví; rizikové faktory; Open Reading Frames; Genetic Predisposition to Disease; analýza přežití; kolorektální nádory; Genetic Association Studies; Case-Control Studies; Česká republika; ženské pohlaví; Survival Analysis; NLR proteiny; Female; regulace genové exprese u nádorů; studie případů a kontrol; Hematopoiesis; Risk Factors